ANALISIS KESULITAN MAHASISWA DALAM MATA KULIAH STATISTIKA DESKRIPTIF - Maysani, Rohmah; Pujiastuti, Heni (Al-Khawarizmi, 2020)
The purpose of this research is to knew the mistaked of the student that took descriptive statistic subject in banking and finance program study. This research used descriptive research method with qualitative approach and the students of banking and finance program study as a subject of this research. The sample of this research consists of ten students who gave the essay test. The result of this research are : 1) the mistake when present the data into appropriate diagram about 30%; 2) the mistake when present the data into distribution frequncy table about 30%; 3) the mistake when present the data into single distribution frequency table about 20%; 4) unconsistency using mathematics simbol about 40%. Besides the mistake was mentioned, there are any another mistake such as the mistake in calculate about 30% and mistake in using formula about 10%. Most of the student was able to comprehend the concept of the statistic descriptive subject, but still inaccurate into calculation and using simbols.